Antimicrobial Potential of Selected Phytochemicals from Hygrophila schulli; Computational Insights - Perera, Pasindu Dilshan; Lawan, Haritha (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2024)
The escalating global concern over antibiotic resistance has led to an intensified exploration of alternative therapeutic strategies, including the utilization of plant-derived secondary metabolites. In this in-silico study, we investigated the structural inhibition of bacterial DNA Topoisomerase IV complex by major secondary metabolites extracted from the medicinal plant Hygrophila schulli. The plant is renowned for its rich phytochemical composition, possessing bioactive compounds with diverse pharmacological properties. Using computational approaches, we conducted molecular docking simulations to explore the binding affinities and interactions between the identified secondary metabolites from Hygrophila schulli and the target bacterial DNA Topoisomerase IV complex. Our results unveil promising interactions, suggesting a potential inhibitory effect on the targeted protein. Furthermore, molecular dynamics simulations were employed to examine the dynamic behavior of the ligand-protein complexes, providing insights into the stability and conformational changes over time. This in-silico exploration contributes valuable information to the understanding of the molecular interactions between plant-derived secondary metabolites and Bacterial DNA Topoisomerase IV, laying the groundwork for future experimental validations. The findings from this study may pave the way for the development of novel antimicrobial agents derived from natural sources, offering a sustainable and effective approach in the ongoing battle against antibiotic-resistant bacterial infections.